2022
DOI: 10.3389/fmicb.2022.899243
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Thrombospondin-Related Paralogous Proteins Rhoptry Discharge Factors 1 and 2 Unveils Phenotypic Plasticity in Toxoplasma gondii Rhoptry Exocytosis

Abstract: To gain access to the intracellular cytoplasmic niche essential for their growth and replication, apicomplexan parasites such as Toxoplasma gondii rely on the timely secretion of two types of apical organelles named micronemes and rhoptries. Rhoptry proteins are key to host cell invasion and remodeling, however, the molecular mechanisms underlying the tight control of rhoptry discharge are poorly understood. Here, we report the identification and functional characterization of two novel T. gondii thrombospondi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Tg277910 and Tg247195 possess one and three thrombospondin type 1 (TSP‐1) domains, respectively (Fig 3C), known to participate in cell adhesion (Adams & Tucker, 2000). In addition, Tg247195 possesses an H‐type lectin domain (Pietrzyk‐Brzezinska & Bujacz, 2020) and, interestingly, has a role in invasion (preprint: Singer et al , 2022; Possenti et al , 2022) and rhoptry secretion (Possenti et al , 2022). To determine the function of Tg277910, we generated an inducible knockdown HA 3 ‐tagged line (Tg277910_iKD; Fig EV3E–G).…”
Section: Resultsmentioning
confidence: 99%
“…Tg277910 and Tg247195 possess one and three thrombospondin type 1 (TSP‐1) domains, respectively (Fig 3C), known to participate in cell adhesion (Adams & Tucker, 2000). In addition, Tg247195 possesses an H‐type lectin domain (Pietrzyk‐Brzezinska & Bujacz, 2020) and, interestingly, has a role in invasion (preprint: Singer et al , 2022; Possenti et al , 2022) and rhoptry secretion (Possenti et al , 2022). To determine the function of Tg277910, we generated an inducible knockdown HA 3 ‐tagged line (Tg277910_iKD; Fig EV3E–G).…”
Section: Resultsmentioning
confidence: 99%
“…berghei , which has been linked to oocyst egress and salivary gland invasion of sporozoites [ 47 ]. In an independent study, it was shown that MIC15 is required for rhoptry discharge and can be partially complemented by its paralog MIC14 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Invasion assay was performed as already described in Possenti et al (77) by differential IFA using a red-green assay (78) by labeling exclusively attached (extracellular) tachyzoites in non-permeabilized samples with anti-TgSAG1 and, after permeabilization with 0.2% Triton X-100, all parasites were stained with rabbit anti-GAP45 antibody. 300 microscopic fields/well at 100× magnification were examined.…”
Section: Methodsmentioning
confidence: 99%